In ovo feeding of L-arginine, succinic acid, and Limosilactobacillus reuteri DSM 17938 enhance intestinal histomorphometric development in broiler via changing yolk utilisation - Habtamu Ayalew; Changchun Xu; Waqar Iqbal; Jing Wang; Shugeng Wu; Kai Qiu; Guanghai Qi; Haijun Zhang (Italian Journal of Animal Science, 2025)
This study investigated the comparative effects of in ovo feeding of L-Arg, succinic acid, and Limosilactobacillus reuteri DSM 17938 on residual yolk, growth, and gastrointestinal tract (GIT) development in broilers. A total of 1260 fertile eggs of Ross 308 breed were incubated by divided into five treatment groups: (1) non-injected control, (2) saline-injected control (0.2 mL/egg), (3) L-Arg (6 mg/egg), (4) succinic acid (2 mg/egg), and (5) L. reuteri DSM 17938 (106 cfu/egg). At 17.5 embryonic days (ED), the solutions were injected into the amniotic sac. A total of 450 male chicks (15 chicks/replicate) were purposively selected and reared for the subsequent 14 days post-hatch. At 19.5 embryonic day, the bioactive substances significantly retained yolk sac weight (YSW) and increased the ratio of YSW to embryo body weight (p < 0.05). Although a significant effect was not observed on body weight, as well as the weight and length of GIT, chicks in the L. reuteri group showed improved feed conversion ratio from 1 to 14 days post-hatch (p < 0.05). Furthermore, both L. reuteri and succinic acid improved villus height (VH), crypt depth (CD), and VH/CD at various post-hatch days (day 4, 7, and 14) (p < 0.05). Notably, succinic acid (2 mg/egg) and L. reuteri (106 cfu/egg) showed comparable positive effects on GIT histomorphometry, suggest their interchangeable use in the broiler industry.Highlights In ovo injection of L-Arg, succinic acid, and Limosilactobacillus reuteri DSM 17938 change yolk sac utilisation. Limosilactobacillus reuteri DSM 17938 improved feed conversion ratio (FCR) from 1-14 days post-hatch. The effect of succinic acid and L. reuteri DSM 17938 on GIT development were comparable.